Measurement of Quasi-Static 3-D Knee Joint Movement Based on the Registration From CT to US - Huang, Qinghua; Yao, Jianan; Li, Jianyi; Li, Meng; Pickering, Mark R.; Li, Xuelong (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2020)
The measurement of quasi-static 3-D knee joint movement is an important basis for studying the mechanism of knee joint injury. Most of the existing measurement methods make use of computed tomography (CT) and nuclear magnetic resonance (MR) imaging technology and hence have the disadvantages of invasiveness, ionizing radiation, low accuracy, and high cost. To overcome those drawbacks, this article innovatively proposes a 3-D motion measurement system for the knee joint based on the registration of CT images to ultrasound (US) images. More specifically, the lower limbs of a subject were first scanned once to acquire the CT images. A portable handheld device was designed to control a US probe for mechanically scanning the subject's lower limbs in a linear trajectory. During the movement of the subject's lower limbs, the US scanning was performed quasi-statically. The acquired US images were then registered to the CT images, and the 3-D motions of the lower limb bones could be recreated with the bones scanned in CT images. To guarantee the registration accuracy and efficiency, we used the H-shaped multiview slice assembly as the structural image content for the registration process. The experimental results show that our approach can accurately measure the 3-D motion of the knee joint and meet the needs of 3-D motion analysis of knee joint in practice.